Democracy beyond borders : justice and representation in global institutions - Kuper, Andrew (Oxford University Press, 2006)
'Democracy Beyond Borders' assesses the philosophical foundations of global order. Developing an innovative political theory of representation, the book provides compelling and practical answers to how we can ensure that global leaders act responsively and effectively in the interests of global citizens.